MEREDUKSI BEBAN ANGIN DENGAN TRANSFORMASI BENTUK TEKNIK EXTRUDE DALAM FOLDING ARCHITECTURE (STUDI KASUS HOTEL MAHKOTA SINGKAWANG) - Gian Vicky Aristo Sinaga; Zairin Zain; Yudi Purnomo (JMARS: Jurnal Mosaik Arsitektur, 2023)
Wind load is one of the main calculations in architectural design, and in the initial process, a designer is more dominant in directing shapes based on structure rather than expressing himself in the form of his design work. While form is the basic element that appears in architectural work, there are various methods of finding forms that have appeared in the development of architectural science. For this reason, the concept of folding architecture is focused on how to process shapes, using the "folding extrude" technique to produce shapes that can reduce the amount of wind load. The object taken in this study is a tall building, with the chosen case study namely the Mahkota Hotel Singkawang, which is the tallest building in West Kalimantan Province. This study raises the simulation process to be carried out by digital simulation with Computational Fluid Dynamics in Autodesk CFD software. The results of this study are from the transformation of the folding extrude technique which has the same shape as one of the architectural elements. From the results of a comparison of the wind load on the surface of ordinary buildings and the results of the folding extrude form, it is proven to be able to reduce wind loads by 15.1%.